APLIKASI E-BUNDLE KEPEGAWAIAIN DINAS PUPR BERBASIS WEB - Ulya, Muhammad Zilfandy; Payana, Mahendar Dwi; Mahendar Dwi Payana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Abstract Banda Aceh City's Public Works and Spatial Planning (PUPR) Department still handles personnel documents by hand using archive bundles. This presents a number of problems, including the possibility of losing crucial documents like employee biodata and decrees (SK), file accumulation, and search difficulties. In order to address these issues, the goal of this project is to develop and construct E-Bundel Staffing, a web-based personnel information system that supports organized, quick, and secure data administration through the use of the PHP CodeIgniter framework and MySQL database. The research methodology is qualitative and combines a system development approach with a literature review, needs analysis, Entity Relationship Diagram (ERD) database design, application implementation, and black-box software testing. With varying access rights for staff, management, and department heads, the study's findings result in an application that may digitally record employee biodata, decree data, and educational histories. It has been demonstrated that this application increases the efficiency of archive administration at the Public Works and Housing Agency (PUPR) of Banda Aceh City, speeds up data retrieval, and reduces the possibility of document loss. Furthermore, This program facilitates the digitalization of local government administration by offering users convenient, real-time, and adaptable access to information at any time and from any location, depending on their needs. This approach improves the overall performance of the organization by making the personnel management process more accountable, transparent, and effective. Additionally, by introducing information technology applications in the public sector, this research helps to set the stage for other government agencies to establish personnel information systems. As a result, the findings of this study have academic value as a reference in the field of informatics, especially with regard to the deployment of web-based information systems to support contemporary and sustainable personnel administration governance, in addition to offering the PUPR Agency of Banda Aceh City practical advantages.